2016
DOI: 10.1016/j.cub.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Rumen Microbiomes in High-Altitude Mammals

Abstract: Studies of genetic adaptation, a central focus of evolutionary biology, most often focus on the host's genome and only rarely on its co-evolved microbiome. The Qinghai-Tibetan Plateau (QTP) offers one of the most extreme environments for the survival of human and other mammalian species. Yaks (Bos grunniens) and Tibetan sheep (T-sheep) (Ovis aries) have adaptations for living in this harsh high-altitude environment, where nomadic Tibetan people keep them primarily for food and livelihood [1]. Adaptive evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
314
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(344 citation statements)
references
References 34 publications
26
314
2
2
Order By: Relevance
“…In the present study, the total VFA concentration was greater in Tibetan than in Han sheep, and, therefore, Tibetan sheep were able to derive more energy than Han sheep from the same feed intake, suggesting a greater degradation of nutrients in the rumen of Tibetan sheep. This was due to, at least in part, the report that rumen microbial genes of Tibetan sheep were richer in VFA‐yielding pathways than Han sheep (Zhang et al, ). The lower rumen pH in Tibetan than in Han sheep was due to the greater VFA accumulation in the rumen (Nikkhah, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the total VFA concentration was greater in Tibetan than in Han sheep, and, therefore, Tibetan sheep were able to derive more energy than Han sheep from the same feed intake, suggesting a greater degradation of nutrients in the rumen of Tibetan sheep. This was due to, at least in part, the report that rumen microbial genes of Tibetan sheep were richer in VFA‐yielding pathways than Han sheep (Zhang et al, ). The lower rumen pH in Tibetan than in Han sheep was due to the greater VFA accumulation in the rumen (Nikkhah, ).…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent transcriptome analysis, Zhang et al () showed higher expression in the high‐altitude species compared with their lowland counterparts for genes that are associated with VFA transport and absorption in the ruminal epithelium. Moreover, a metagenomic analysis of the rumen in both Tibetan sheep and yak revealed co‐enrichment in VFA‐yielding pathways of rumen microbial genes, which further indicates a co‐evolution of the microbiome and the host genome in response to altitude adaptation (Zhang et al ).…”
Section: Genetic Background Of High‐altitude Adaptationmentioning
confidence: 99%
“…The Qinghai‐Tibetan plateau provides one of the most extreme environments for the survival of humans and other mammals (Zhang et al . ). The Tibetan wild ass ( Equus kiang ) is a unique species on the Qinghai‐Tibetan plateau and is widely distributed in Qinghai, Gansu, Xinjiang, Sichuan and Tibet (Wu and Yi ; Moehlman ).…”
Section: Introductionmentioning
confidence: 97%